Evaluation of Entrepreneurship Education Pedagogical Content Knowledge for Business Education Students’ Business Start-Up in Abubakar Tafawa Balewa University, Bauchi - Adamu, I. A.; Abdulmutallib, , U. B. (Kashere Journal of Education, 2021)
The aim of the study was to Evaluate Entrepreneurship Education Pedagogical Content Knowledge for Business Education Students Business Start-Up in a Abubakar Tafawa Balewa University Bauchi, the study adopted quantitative research and the design used for the study was descriptive study. The population of the study is 526 of all undergraduate business education students; the instrument used to elicit response from the respondents was a validated structured questionnaire. The total population of 526 was used as the sampling size therefore purposeful sampling technique was used. The researcher with the help of two (2) research assistants administered the questionnaire. Data collected were analyzed using mean and standard deviation. The result of the study revealed that the pedagogical content knowledge of entrepreneurship education influence business education students’ business start-up which emphasizes in Developed entrepreneurial mind-set, Developed entrepreneurship knowledge, Help redefine conceptual barriers, Effective content delivery, Making the subject comprehensible, Useful form of presentation of ideas, Bridges content knowledge and practice of teaching, Develop entrepreneurial competence, Explicate the best method for transmitting knowledge and Enhance teaching and learning for business start-up. The result further revealed that it Instil entrepreneurial intention, develop entrepreneurial mind-set, inculcate entrepreneurial skills, increase motivation, increase ability to participate, help in making better decision, develop better understanding of entrepreneurship education, relate theoretical aspect of entrepreneurship education into practical, measure the impacts of entrepreneurship education, prepare business education students to face challenges of business start-up. Based on the findings of the study, it was recommended that Government, National Universities Commission (NUC), Federal Ministry of Education, Universities and Lecturers should ensure the use of entrepreneurship education pedagogical content knowledge in teaching business education students for business start-up and also provide training through organizing, workshops, seminars and put more emphasis on the use of entrepreneurship education pedagogical content knowledge for the teachers of business education in universities in North east, Nigeria